From human to post human security in Latin America : examples and reflections from across the region - Ibarrarán, María Eugenia; Aguilar, José Garcia (Emerald Publishing Limited, 2021)
Current political discourse emphasizes the globalized nature of security threats, and focusing on Latin America, this book identifies local complexities of Human Security. From Human to Post Human Security in Latin America provides a fresh look to some acute problems regarding human security in Latin America: human rights and dignity, water, food and health insecurities. These problems are persistent and constitute human security threats in the near future. In this book, each chapter studies a critical social problem in Latin America and analyzes it from the human security perspective, providing examples that illustrate the critical state in which Latin America is found regarding environmental security and providing a comparative perspective to give a wider view of these issues. Now security threats are truly global; given the limits of the international community and the nation state to solve these issues, it is necessary to revisit the most acute problems that the planet faces from a more comprehensive perspective. This is essential reading for professionals in the field of policy making, practitioners with a need of a conceptual support, and those interested in human security in Latin America from a Latin American perspective.